Factors Affecting Nurse Anxiety During The Covid-19 Pandemic - Yeni Yulistanti; Dwi Yuliantuti Prasetyaningtyas; Lulut Handayani (Midwifery and Nursing Research, 2022)
Background: The covid-19 pandemic that has occurred in almost all countries in the world has had an impact on various aspects of life. Indonesia as one of the countries facing the covid-19 pandemic is still showing an increase in the number. Patients with covid-19 require appropriate treatment, especially if the patients shows severe symptoms of respiratory system disorders. Nurses as health care providers in hospital are required to provide the best and professional service. Nurses are faced with situations that can increase stress and anxiety. It is necessary to conduct an assessment of the factors that cause anxiety in nurses during the covid-19 pandemic. Methods: This study aims to determine the factors that influence nurses' anxiety during the COVID-19 pandemic. This research is a descriptive analytic study with a cross sectional study design. The population in this study were all nurses at dr. Asmir Salatiga Hospital. The instrument used to assess the level of anxiety using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis using chi square test. Results: Among the 7 factors studied, there are 4 factors that have been shown to affect nurses anxiety. The factor that influences the nurse’s anxiety during covid-19 pandemic are years of service (p value 0.047), marital status (p value 0.048), knowledge (p value 0.042) and environment (0.039). Conclusion: The factors that influence the nurse’s anxiety during covid-19 pandemic are years of service, marital status, knowledge and environment with p